2022
DOI: 10.3389/fimmu.2022.972121
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of defects in immune tolerance underlying the development of autoimmunity

Abstract: Genetic variants associated with susceptibility to autoimmune disease have provided important insight into the mechanisms responsible for the loss of immune tolerance and the subsequent development of autoantibodies, tissue damage, and onset of clinical disease. Here, we review how genetic variants shared across multiple autoimmune diseases have contributed to our understanding of global tolerance failure, focusing on variants in the human leukocyte antigen region, PTPN2 and PTPN22, and their role in antigen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
0
9
0
5
Order By: Relevance
“…Thus, autoimmunity is most likely central for physiological homeostasis and should not be confused with autoimmune diseases. As such, not all autoreactive B cells are pathogenic and additional elements including genetic and environmental factors, would be required for the development of autoimmune diseases (53,54). Similarly, although RFs are mostly associated with RA, several studies have shown that they can also be found in sera of healthy individuals suggesting that their presence does not necessarily lead to disease pathogenesis (12,19,20,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, autoimmunity is most likely central for physiological homeostasis and should not be confused with autoimmune diseases. As such, not all autoreactive B cells are pathogenic and additional elements including genetic and environmental factors, would be required for the development of autoimmune diseases (53,54). Similarly, although RFs are mostly associated with RA, several studies have shown that they can also be found in sera of healthy individuals suggesting that their presence does not necessarily lead to disease pathogenesis (12,19,20,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…2023; 3:304 2 varios para dar inicio a este proceso. (8) El fenotipo de las enfermedades autoinmunes es heterogéneo presentando alrededor de 80 tipos como son: artritis reumatoidea, esclerosis sistémica, enfermedad de Graves, tiroiditis de Hashimoto, síndrome de Sjögren, lupus, etc. En base a esta diferenciación de padecimientos, durante la última década los estudios de asociación de genoma completo (GWAS) han permitido la determinación de diversos factores de riesgo.…”
Section: Autoinmunidadunclassified
“…(24) Goulielmos et al (21) mencionan que los polimorfismos asociados a LES según la descendencia ancestral son: PTPN22, TNFAIP3-TNIP1, TNFSF4, IRF5, IRF7, IRF8, MAVS y TREX1. Tizaoui et al (1) detallan que el polimorfismo de la proteína tirosina fosfatasa no receptora de tipo 22 (PTPN22), la misma que constituye un regulador de la activación de las células T, estaría implicado en el desarrollo de LES al provocar un cambio en la codificación de la proteína tirosina fosfatasa (Lyp) dando paso a: una sobreexpresión del receptor de linfocitos T, la activación espontánea de los mismos, así como la estimulación de anticuerpos anti-CD3; por su parte, Hocking et al (8) señalan que tendría implicación en distintas células de la inmunidad, además de linfocitos; células natural killer, neutrófilos, macrófagos y Salud, Ciencia y Tecnología. 2023; 3:304 4 células dendríticas mediado por una variante polimórfica del PTPN22 que produce sustitución de una timina por una citosina cambiando la arginina por triptófano modificando la composición del compartimento de células B e incrementando la cantidad de células auto y poli reactivas en sus portadores, fallando por tanto la tolerancia de las células B; así también, Goulielmos et al (21) complementan al detallar que las poblaciones específicas afectadas por este gen serían los europeo-americanos e hispanos.…”
Section: Lupus Eritematoso Sistémicounclassified
See 2 more Smart Citations